IMPLEMENTASI MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN KETERAMPILAN PSIKOMOTOR SISWA PADA MATA PELAJARAN PJOK DI SEKOLAH MENENGAH PERTAMA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to review the implementation of digital learning media in improving students' psychomotor skills in Physical Education (PJOK) at the junior high school level. The research employed a literature review method by analyzing ten national journal articles published between 2022 and 2025 that are relevant to the topic. The findings indicate that digital media such as instructional videos, interactive multimedia, e-modules, Android-based learning applications, and gamification platforms significantly enhance students’ ability to understand basic movement techniques, increase learning motivation, and strengthen engagement during the learning process. The use of digital media also helps address limitations in learning facilities and offers flexible access to learning resources. However, challenges such as limited devices and teachers’ digital competence still arise. Overall, digital learning media have been proven to be effective in supporting the development of junior high school students’ psychomotor skills in PJOK learning.